A systematic review of outcome reporting and outcome measures in studies investigating uterine-sparing treatment for adenomyosis. Issue 3 (7th August 2021) - Tellum, T; Omtvedt, M; Naftalin, J; Hirsch, M; Jurkovic, D
Abstract: STUDY QUESTION: Which outcomes and outcome measures are reported in interventional trials evaluating the treatment of adenomyosis? SUMMARY ANSWER: We identified 38 studies, reporting on 203 outcomes using 133 outcome measures. WHAT IS KNOWN ALREADY: Heterogeneity in outcome evaluation and reporting has been demonstrated for several gynaecological conditions and in fertility studies. In adenomyosis, previous systematic reviews have failed to perform a quantitative analysis for central outcomes, due to variations in outcome reporting and measuring. STUDY DESIGN, SIZE, DURATION: A systematic search of Embase, Medline and Cochrane Register of Controlled Trials (CENTRAL) was performed with a timeframe from 1950 until February 2021, following the preferred reporting items for systematic reviews and meta-analysis (PRISMA). PARTICIPANTS/MATERIALS, SETTING, METHODS: Studies reporting on any uterus-sparing intervention to treat adenomyosis, both prospective and retrospective, were eligible for inclusion. Inclusion criteria were a clear definition of diagnostic criteria for adenomyosis and the modality used to make the diagnosis, a clear description of the intervention, a follow-up time of ≥6 months, a study population of n ≥ 20, a follow-up rate of at least 80%, and English language. The population included premenopausal women with adenomyosis. Risk of bias was assessed using the Evidence Project risk of bias tool. MAIN RESULTS AND THE ROLE OF CHANCE: We included 38 studies (6 randomized controlled trials and 32 cohort studies), including 5175 participants with adenomyosis. The studies described 10 interventions and reported on 203 outcomes, including 43 classified as harms, in 29 predefined domains. Dysmenorrhoea (reported in 82%), heavy menstrual bleeding (HMB) (in 79%) and uterine volume (in 71%) were the most common outcomes. Fourteen different outcome measures were used for dysmenorrhoea and 17 for HMB. Quality of life was reported in 9 (24%) studies, patient satisfaction with treatment in 1 (3%). A clear primary outcome was stated in only 18%. LIMITATIONS, REASONS FOR CAUTION: This review includes studies with a high risk of bias. WIDER IMPLICATIONS OF THE FINDINGS: Shortcomings in the definition and choice of outcomes and outcome measures limit the value of the conducted research. The development and implementation of a core outcome set (COS) for interventional studies in adenomyosis could improve research quality. This review suggests a lack of patient-centred research in adenomyosis and people with adenomyosis should be involved in the development and implementation of the COS. STUDY FUNDING/COMPETING INTERESTS: No funds specifically for this work were received. T.T. receives fees from General Electrics for lectures on ultrasound independently of this project. TRIAL REGISTRATION NUMBER: This review is registered with the International Prospective Register of Systematic Reviews (PROSPERO; registration number CRD42020177466) and the Core Outcome Measures in Effectiveness Trials (COMET) initiative (registration number 1649).